A phytogeographic analysis of birch woodlands in the southern part of West Siberia - NIMIS, PIERLUIGI; Malyshev L. I.; Bolognini G. (Vegetatio, 1994)
A minimum variance cluster analysis of 87 species of vascular plants occurring in south Siberian birch woodlands, based on their total distribution ranges, grouped them into 9 phytogeographic elements. The main distribution patterns of each element are illustrated by means of maps obtained by automatic mapping programs, showing the joint occurrence of the species of each element on a world scale. The results indicate a predominance of Eurasiatic-temperate taxa. The south Siberian birch woodlands can be considered as the easternmost extensions of the European deciduous forest belt, which in Siberia is compressed between the taiga biome in the north and the steppe biome in the south. The marginal position of Siberian Betula stands is reflected by the persistence of plants which are 'ecologically marginal' with respect to true forest vegetation; most of the Eurasiatic species are typical, in Europe, of forest-meadows and forest-margins.